2020
DOI: 10.3906/elk-1907-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network based m-learning model for predicting mobile learners’ performance

Abstract: The use of deep learning (DL) techniques for mobile learning is an emerging field aimed at developing methods for finding mobile learners' learning behavior and exploring important learning features. The learning features (learning time, learning location, repetition rate, content types, learning performance, learning time duration, and so on) act as fuel to DL algorithms based on which DL algorithms can classify mobile learners into different learning groups. In this study, a powerful and efficient m-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The activation function used in the last dense layer is sigmoid, which outputs probabilities of both the classes. Dropout is used between convolution 1D layer and max pooling layer and then between last two dense layers [37]. Its step-wise description is given in Algorithm 1. end for 15: end procedure…”
Section: ) Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…The activation function used in the last dense layer is sigmoid, which outputs probabilities of both the classes. Dropout is used between convolution 1D layer and max pooling layer and then between last two dense layers [37]. Its step-wise description is given in Algorithm 1. end for 15: end procedure…”
Section: ) Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…Mobile devices can help students in learning a foreign language in those situations where the several challenges and students are not aware of the new language [25]. M-learning can provide optimal conditions for students to enhance their engagement while learning the target language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As stated previously, RF algorithm suffers from determination of the optimal hyper-parameter and in this study the RF and PR are integrated with ICO for improving the results and develop robust algorithms. It is already reported that each tree in a RF model can grow incorrectly and reduced the prediction accuracy of the model (Adnan et al 2019) node are two operators from these hyper-parameter which significantly affect the RF prediction power. To this end, ICO algorithm was implemented to determine the best subset of features in RF model to enhance the result.…”
Section: Iterative Classifier Optimizermentioning
confidence: 99%